LOGISTICS POTENTIAL OF WESTERN UKRAINE REGIONS - Khvyshchun N.V., (Pressing Problems of Public Administration, 2016)
In this article we have done the analysis of Ukraine according to the logistic performance index andhave assessed logistic potential of border regions of Western Ukraine in order to identify strategicdirections of state and regional management.